Distress Tolerance and Emotion Regulation as Potential Mediators Between Secondary Traumatic Stress and Maladaptive Coping - Benuto, Lorraine T. (Journal of interpersonal violence, 2022)
The extant literature has illustrated that protective service workers experience negative repercussions associated with their job (including the development of secondary traumatic stress; STS) and may utilize maladaptive coping mechanisms. Developing an improved understanding of factors that might explain the relationship between STS and the utilization of maladaptive coping mechanisms is warranted. This study sought to examine emotion regulation and distress tolerance as potential mediators between STS and the utilization of maladaptive coping mechanisms. Participants were 152 elder protective service workers and 105 child protective service workers who completed an online survey of self-report measures of emotion regulation, distress tolerance, STS, and coping behaviors. A parallel multiple mediator model was analyzed using structural equation modeling (SEM) to examine the hypothesis that distress tolerance and emotion regulation would mediate the relationship between STS and the utilization of maladaptive coping. Our hypothesis was partially supported as the effect of STS on maladaptive coping was mediated by emotion regulation but not by distress tolerance. The results from this study have both prevention and intervention implications. From a prevention perspective, efforts could be directed at teaching emotion regulation skills to those at risk for developing STS as a mechanism for decreasing the probability of denial, substance use, behavioral disengagement, and self-blame that may occur as a consequence of STS. From an intervention perspective, some of the negative sequelae of exposure to STS may be averted by teaching EPS and CPS workers who present with STS symptoms, emotion regulation skills.